Peran Auditor Internal dalam Meningkatkan Kualitas Laporan Keuangan di LAZ Mizan Amanah - Rohman, Dadan; Amrizal, Amrizal; Gusneli, Dea (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the role of internal auditors in improving the quality of financial reports at the Mizan Amanah Zakat Institution (LAZ). The research method used is a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation studies. Research informants consisted of internal auditors, financial management, and the leadership of LAZ Mizan Amanah. Data analysis was carried out using triangulation techniques to ensure the validity and reliability of the research results. The results of the study indicate that internal auditors at LAZ Mizan Amanah have a strategic role in improving the quality of financial reports through several aspects: (1) Conducting periodic reviews and evaluations of internal control systems; (2) Ensuring compliance with sharia accounting standards and applicable regulations; (3) Providing recommendations for improvements to system weaknesses found; (4) Monitoring the implementation of consistent accounting policies; and (5) Acting as an early warning system to prevent material errors in financial reports. Internal auditors have a vital role in improving the quality of LAZ Mizan Amanah's financial reports through effective monitoring, evaluation, and consultation functions. This study recommends the need to strengthen the capacity of internal auditors, increase the independence of the internal audit function, and develop an integrated accounting information system to support the preparation of higher quality financial reports.